Efficacy of Treatments Targeting Hypothalamic-Pituitary-Adrenal Systems for Major Depressive Disorder: A Meta-Analysis - Ding, Yudan; Wei, Zirou; Yan, Haohao; Guo, Wenbin (Frontiers in Pharmacology, 2021)
Abnormal hypothalamic-pituitary-adrenal (HPA) axis has been implicated in major depressive disorder (MDD). A number of studies have attempted to use HPA-modulating medications to treat depression. However, their results are inconsistent. The efficacy of these drugs for MDD remains uncertain. The aims of this meta-analysis were to determine the effect and safety profile of HPA-targeting medications for MDD. World of Science and PubMed databases were comprehensively searched up to March 2021. All randomized controlled trials (RCTs) and open-label trials exploring antiglucocorticoid and related medications in patients with depression were included. Standardized mean differences (SMDs) and risk ratios (RRs) with 95% confidence intervals (CIs) were calculated for continuous or dichotomous outcomes, respectively. In the meta-analysis, we identified 16 RCTs and seven open-label studies that included 2972 subjects. Pooling the change data that assessed the efficacy across all included HPA-targeting medications for depression showed a significant difference between interventions and controls with very small heterogeneity after influence analysis (SMD = 0.138, 95%CI = 0.052, 0.224, p = 0.002; I2 = 20.7%, p = 0.212). No obvious publication bias was observed (p = 0.127). Effectiveness remained significant in patients with MDD (SMD = 0.136, 95%CI = 0.049, 0.223, p = 0.002). Subgroup analysis showed a significant difference favoring mifepristone and vasopressin 1B (V1B) receptor antagonist treatment. Adverse events were reported by 14 studies and our analysis of high-quality studies showed a significant difference in favor of controls (RR = 1.283, 95%CI = 1.134, 1.452, p = 0). Our study suggested that patients with MDD may benefit from mifepristone and V1B receptor antagonist treatments that have tolerable side effects. HPA-based medications are promising for depression treatment. However, additional high-quality RCTs, including head-to-head trials, are needed.